Tracheal Smooth Muscle Cells Stimulated by Stem Cell Factor-c-Kit Coordinate the Production of Transforming Growth Factor-β1 and Fibroblast Growth Factor-2 Mediated by Chemokine (C-C Motif) Ligand 3 - De Oliveira, Luis Cezar Farias [UNESP]; Danilucci, Taï¿½s Marolato [UNESP]; Chaves-Neto, Antonio Hernandes [UNESP]; Campanelli, Ana Paula; Da Silva, Tereza Cristina Cardoso [UNESP]; Oliveira, Sandra Helena Penha [UNESP] (SAGE Publications, 2016)
The aim of this study was to evaluate the mechanism involved in the stem cell factor (SCF)-induced production of fibroblast growth factor-2 (FGF-2), transforming growth factor-β1 (TGF-β1), and chemokine (C-C motif) ligand 3 (CCL3) in tracheal smooth muscle cells (tSMCs) and the signaling pathway involved in the process. tSMC primary cultures were stimulated with SCF and evaluated at 24 h. Cells treated with specific antibodies did not show any immunolabeling for cytokeratin or fibroblast activation protein, but were positive for α-smooth muscle actin, indicating the purity of the primary cell line. Western blot analysis showed constitutive phosphorylation of c-Kit, as well as increased total protein and phosphorylated c-Kit levels in tSMCs after SCF stimulation. Flow cytometry analysis also showed an increase in cell-surface c-Kit expression in the presence of SCF. SCF induced TGF-β mRNA expression in tSMCs, as well as the production of TGF-β1, CCL3, and FGF-2. Pretreatment with anti-CCL3 antibody blocked TGF-β1 expression and partially inhibited FGF-2 production. On the other hand, anti-c-Kit antibody blocked TGF-β1 expression and FGF-2 production. Thus, TGF-β1 and FGF-2 production were mediated by CCL3 production through c-Kit. Pretreatment with mitogen-activated protein kinase kinase 1, p38, and Jun N-terminal kinase inhibitors showed that the effects mediated by SCF were involved with the modulation of mitogen-activated protein kinase (MAPK) pathways. Development of inhibitors targeting CCL3 through MAPK activation could thus be an attractive strategy to inhibit tSMC activation during asthma.